Weather-based epidemiological models for Sclerotinia rot of oilseed Brassicas for Rajasthan - N. AHMAD, N. MEHTA, D.K. YADAVA and C. CHATTOPADHYAY, M.S. YADAV*, AMRENDER KUMAR, S. GODIKA (Indian Phytopathology, 2016)
Sclerotinia rot {Sclerotinia sclerotiorum (Lib.) de Bary} of oilseed Brassicas is an emerging problem in Rajasthan. Quantitative models were developed for prediction of Sclerotinia rot on Brassicas. Historical data from 2004-05 to 2014-15 on per cent Sclerotinia rot and weekly weather variables of SKRAU, Agricultural Research Stations in Alwar and Sriganaganagar, Rajasthan were considered for model fitting. Weather-based indices were generated which were used as explanatory variables. Different weather variables viz., minimum and maximum temperatures and afternoon relative humidity were identified as critical factors which significantly affected the development of Sclerotinia rot of oilseed Brassicas. The coefficient of determination (R2) were maximum 0.93 and 0.88 at Sriganganagar and Alwar, respectively. Prediction-based management advisory to farmers could be issued with information for timely application interventions of pesticides to manage Sclerotinia rot.